Proceedings of the Seventh International Conference on Technological Ecosystems for Enhancing Multiculturality 2019
DOI: 10.1145/3362789.3362918
|View full text |Cite
|
Sign up to set email alerts
|

How to Measure Teachers' Acceptance of AI-driven Assessment in eLearning

Abstract: The use of AI is becoming a growing reality the educational field. One of the activities in which it is beginning to be implemented is the assessment of student achievement. This way, we can find in the literature an increasing number of investigations focused on the possibilities offered by the adoption of AI-driven assessment. However, the use of AI is also a source of concern that raises suspicions in some sectors of our society. In this context, knowing the position of the teachers towards this topic is cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The TAM is a useful framework that is used to understand adoption of new technologies in diverse contexts, such as the smartphones (Park & Chen, 2007), social media (Choi & Chung, 2013), and virtual reality (Lin & Yeh, 2019;Sagnier et al, 2020). Although very limited, the TAM has been also employed to understand the adoption of AI-based assessment in education (Cruz-Benito et al, 2019;Sánchez-Prieto et al, 2019). However, the use of TAM in these studies was limited to proposing theoretical arguments without empirical support.…”
Section: Contributions and Implicationsmentioning
confidence: 99%
“…The TAM is a useful framework that is used to understand adoption of new technologies in diverse contexts, such as the smartphones (Park & Chen, 2007), social media (Choi & Chung, 2013), and virtual reality (Lin & Yeh, 2019;Sagnier et al, 2020). Although very limited, the TAM has been also employed to understand the adoption of AI-based assessment in education (Cruz-Benito et al, 2019;Sánchez-Prieto et al, 2019). However, the use of TAM in these studies was limited to proposing theoretical arguments without empirical support.…”
Section: Contributions and Implicationsmentioning
confidence: 99%
“…Greater knowledge on the use of ICT in teaching and learning exposes teachers to what new practices look like (Barakabitze et al, 2019). Perceived ease of use represents the extent to which mathematics teachers believe that the integration of ICT into teaching and learning was less stressful (Sánchez-Prieto et al, 2019;Weng et al, 2018) and was found to positively influence both perceived usefulness and teachers' attitude towards the use of ICT. The findings were similar to that of Hamid et al (2016) who also identified that perceived ease of use significantly predicted attitude towards the use of ICT in teaching and learning.…”
Section: Discussionmentioning
confidence: 99%
“…The use of TAM in assessing the adoption of ICT in educational setting has been studied by a number of researchers. Sánchez-Prieto et al (2019) measured teachers' acceptance of AI-driven assessment in e-learning, included AI anxiety and relative advantage as added variables to the original TAM. Dele-Ajayi et al (2017) added external factor (ICT experience) as an extension of TAM in assessing digital educational games acceptance by teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Although various research has been conducted in e-learning adoption by students (Gupta and Priyanka, 2022; Raman et al ., 2014), MOOC adoption (Altalhi, 2021), LMS adoption (Farooq et al. , 2017), ICT adoption in education (Sánchez-Prieto et al ., 2019) etc. but there are a very few studies available in virtual communication adoption by educational leaders in the perspective of e-leaders (Van Wart et al ., 2019).…”
Section: Literature Reviewmentioning
confidence: 99%